Civil Construction Scenario in Brazil during the COVID-19 Pandemic (Research, Society and Development, 2020)
This research aims to present the current scenario of Civil Construction in some Brazilian states, showing the places that established the sector's halt and those that continued to operate normally, being made a comparison taking into account the demographic density of the states and the higher and lower number of deaths to date and also demonstrating the measures adopted on construction sites to prevent the spread of the disease. The research method was based on data collected at the State Health Secretariats and Construction Industry Unions (Sinduscon) of the states, from newspapers and magazines in 8 Brazilian states, 4 of which have the lowest number of deaths and 4 have the highest number of registered deaths. It was generating a value, called index "I" (Deaths / Demographic Density), this way it was possible to understand the impact that the Civil Construction industry can bring to the propagation of COVID-19, since the Civil Construction sector moves the other sectors, such as construction material stores, distributors, restaurants, public transportation, among others. It was verified which States the Civil Construction sector is complying with the paralysis of the sector and compare data from the States with the highest rates of this disease, verifying if there is any correlation for the increase of confirmed cases. The states with the highest number of deaths were SP > RJ > CE > PE, but their indexes were different, relating them to the control or lack of control of virus prevention in civil construction and other sectors, where if compared with index "I" the sequence is SP > CE > PE > RJ, being I = 13.57 for São Paulo and the states with the lowest number of deaths were TO < MS < MT < AC and their comparisons by index "I" continue in the same sequence, with Tocantins with the lowest index among all states, I = 0.53. Some essential measures were adopted to avoid the spread of coronavirus, such as the use of thermometers at the entrance to the work, marking on the floor to keep people away, distance between the tables and removal of intermediate seats, sanitization of work sites, distribution of information posters throughout the work site, shift redefinition, among other measures are very important for the welfare and health of workers.